FACTORS INHIBITING STUDENTS’ ENGLISH-SPEAKING PERFORMANCE AT JUNIOR HIGH SCHOOL LEVEL - Gracia Putri Kinanti; Chairil Anwar Korompot; Nur Aeni (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This study aimed to identify the inhibiting factors affecting students’ English-speaking performance. A descriptive qualitative design was employed to obtain an in-depth understanding of students’ experiences. The research was conducted at SMP Negeri 4 Sungguminasa, involving six eighth-grade students selected through purposive sampling. Data were collected through semi-structured in-depth interviews and analyzed using thematic analysis. The findings revealed eight inhibiting factors affecting students’ English-speaking performance, namely pronunciation difficulties, limited vocabulary, fear of negative evaluation, lack of exposure to English, teacher’s teaching styles, classroom conditions, grammar mastery, and negative past experiences. The findings also indicate that inhibiting factors are not only related to cognitive limitations but also arise from the interaction of affective, cognitive, psychological, and environmental factors during the speaking process. This study is expected to contribute to teachers’ understanding of students’ speaking difficulties and to support the development of more responsive and supportive speaking instruction strategies.Keywords: English speaking performance; inhibiting factors; junior high school students